Younger Relative Metabolic Age Is Associated with a More Favorable Body Composition and Plant-based Dietary Pattern (P21-038-19). (13th June 2019) - Andersen, Catherine; Sloan, Allison; Dupree, Lydia; Walker, Brian
Abstract: Objectives: Metabolic age serves as an emerging marker for metabolic health. We investigated whether relative metabolic age, defined as an individual's metabolic age relative to their chronological age, was associated with markers of body composition, blood pressure, and dietary intake. Methods: Adult men and women (18–70y, n = 19) participated in a fasted baseline health assessment to measure body composition, waist circumference, resting blood pressure, and metabolic age using a Tanita SC-240 scale and Health Ware software. Dietary analysis of 5-day diet records was performed using Nutrition Data System for Research (NDSR), and satiety was quantified using a subjective scale. Relative metabolic age was calculated as: metabolic age – chronological age. Subjects were subsequently divided into two groups: young relative metabolic age ( n = 10) and advanced relative metabolic age ( n = 9). Results: Relative metabolic age was significantly greater in the advanced relative metabolic age (+5 years) compared to the younger relative metabolic age group (−12 years), whereas chronological age and non-adjusted metabolic age did not differ between groups. Individuals with younger relative metabolic age had significantly lower body weight, body mass index, body fat mass, and waist circumference on average. Systolic blood pressure was additionally lower in subjects with a younger relative metabolic age. In evaluating diet composition, individuals with advanced relative metabolic age reported greater cravings for fat-rich foods, and consumed greater amounts of pork and cold cuts/sausages. Conversely, individuals with a younger relative metabolic age consumed significantly more grains, lauric acid, meat alternative, a greater percentage of calories from polyunsaturated fatty acids, and trended toward consuming greater amounts of vegetable protein. Conclusions: These findings suggest that younger relative metabolic age is associated with a more favorable body composition, lower blood pressure, and a plant-based dietary pattern. Funding Sources: This study was funded by the Fairfield University College of Arts and Sciences.